1996
DOI: 10.1016/s0741-5214(96)70072-1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of routine carotid duplex screening in patients who have claudication

Abstract: The recently published Asymptomatic Carotid Atherosderosis Study (ACAS) demonstrated the benefit of performing carotid endarterectomy in selected asymptomatic patients who have >60% carotid stenoses. It therefore becomes clinically important to identify the subgroups of patients who have a sufficiently high incidence of high-grade carotid stenosis to warrant routine carotid duplex screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
3
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 15 publications
1
40
3
1
Order By: Relevance
“…There is ongoing controversy about the value of screening all patients with PAOD, symptomatic or not, for carotid disease and aortic aneurysms [35,36]. Based on duplex sonography, carotid disease could be demonstrated in 26 to 50% of patients with PAOD [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing controversy about the value of screening all patients with PAOD, symptomatic or not, for carotid disease and aortic aneurysms [35,36]. Based on duplex sonography, carotid disease could be demonstrated in 26 to 50% of patients with PAOD [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…17) Conversely, the frequencies of concurrence of CS in CAD and PAD patients have also been reported. 11,29) Kawarada et al 16) observed that CAD was complicated by CS in 13.7% and by PAD in 15.3% of the 380 patients who underwent elective CABG and reported the necessity of screening patients with cardiovascular risk factors for atherosclerotic diseases. 11) Marek et al 29) performed carotid artery ultrasound in 188 patients showing claudication with no history of cerebrovascular disorder and reported that ≥50% internal CS was noted in 24.5% and that it was occluded in 2.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary heart disease has been already shown to represent only a part of a more generalized atherosclerotic disease, and a clear correlation [6,7,29,31] has been found between extent of coronary artery disease and incidence of carotid and/or peripheral vascular disease. Nevertheless there is still a lack of guidelines about which preoperative vascular investigations should be performed in a patient undergoing CABG: some authors [18,21] are limiting preoperative vascular investigations to those patients with symptoms and/or clinical signs of associated vascular disease (e.g. carotid bruit or peripheral pulse losses); others [2,9,13,16], in order to prevent and reduce the incidence of postoperative cerebrovascular events, are performing routinely preoperative Echo-Doppler screening of carotid vessels.…”
Section: Introductionmentioning
confidence: 99%